Stimulating effect of guanidinium-based cationic polymer on wheat seedlings growth - Rogalsky, Sergiy; Tarasyuk, Oksana; Lyoshina, Lyudmila; Bulko, Olga; Kuchuk, Mykola (Problems of Environmental Biotechnology, 2021)
The growth-promoting activity of poly(DEG-GH) was studied using a test-culture of winter wheat Podolianka. Wheat seeds were soaked in water solutions of cationic polymer for 1 h, placed into Petri dishes and germinated on filters, moistened with distilled water. After seven days, the length of shoots of the seedlings, soaked in poly(DEG-GH) solutions with the concentration of 0.001 % and 0.01 %, was higher compared to control samples (by 6.7 % and 17.8 %, respectively). The maximum increase in the length of seedling roots (14.5 % compared to the control) was established for the lowest cationic polymer concentration of 0.001 %. The concentration of poly(DEG-GH) of 0.1 % inhibited the growth of roots and shoots by 28 % and 18 %, respectively. Thus, the cationic polymer poly(DEG-GH) demonstrates growth-promoting activity on wheat seedlings in the low concentration range of 0.001–0.01 %.